Weekly Energy Management of a Smart Home based on the Internet of Things - Ahmed Chfat Abd Zaid (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Energy management and related issues are perhaps the most important challenges facing electricity distribution companies in the modern era. Optimizing energy consumption in smart homes has attracted the attention of advanced countries in recent years due to their ability to reduce carbon dioxide gas produced from fossil fuels. For this purpose, in this study, planning the energy management of a smart home based on the Internet of Things to investigate its effect on reducing the weekly cost of energy consumption of a smart home in normal mode and reducing the amount of energy not supplied when the smart home is disconnected from the network, with it is suggested to consider the behavior of household consumers for energy planning during a week. In this study, in addition to considering the role of controllable and uncontrollable household loads in improving the technical and economic goals of the smart home, from distributed energy resources such as energy storage system (ESS), plug in hybrid electric vehicle (PHEV), photovoltaic system (PV) and wind turbine (WT) have been used in smart home energy management. In this research, the linearization of non-linear mathematical equations has been used to reduce the calculation time and reduce the complexity of the calculations. In this study, the smart home is examined in normal mode and in the mode of disconnection from the main network. The results show that the presence of energy resources in smart homes and the optimal energy management of household loads can have an effective effect on reducing the cost of energy consumption and the energy not supplied.